Trading Off Co-produced Marine Ecosystem Services: Natural Resource Industries Versus Other Use and Non-use Ecosystem Service Values - Aanesen, Margrethe; Armstrong, Claire W. (Frontiers in Marine Science, 2019)
Ecosystem services (ES) may be both non-market and market based. Both may provide important input to societal welfare. Using natural resources, or converting nature in the development of market based ES may impact the access to non-market or more conservationist ES, and vice versa. How does the general public trade-off between these two types of ES? We use two valuation studies in Northern Norway to identify the public’s preferences for marine industries versus other marine use and non-use values. One study assesses willingness to pay to protect cold-water corals, a relatively abundant, and to some degree, protected resource off the coast of Norway. The other study elicits people’s willingness to pay for stricter regulations of industrial activity in the coastal zone, providing more coastal area for recreational activities. Both studies show strong conservation preferences, and willingness to forego blue industrial growth. However, these preferences are heterogeneous across socio-economic characteristics, and, interestingly, educational level is the characteristic that most distinctly separates the population into various preference groups.